Left Ventricular Mass, Brain Magnetic Resonance Imaging, and Cognitive Performance: Results From the Strong Heart Study. Issue 5 (November 2017) - Haring, Bernhard; Omidpanah, Adam; Suchy-Dicey, Astrid M.; Best, Lyle G.; Verney, Steven P.; Shibata, Dean K.; Cole, Shelley A.; Ali, Tauqeer; Howard, Barbara V.; Buchwald, Dedra; Devereux, Richard B.
Abstract : Left ventricular mass (LVM) has been shown to serve as a measure of target organ damage resulting from chronic exposure to several risk factors. Data on the association of midlife LVM with later cognitive performance are sparse. We studied 721 adults (mean age 56 years at baseline) enrolled in the Strong Heart Study (SHS, 1993–1995) and the ancillary CDCAI (Cerebrovascular Disease and Its Consequences in American Indians) Study (2010–2013), a study population with high prevalence of cardiovascular disease. LVM was assessed with transthoracic echocardiography at baseline in 1993 to 1995. Cranial magnetic resonance imaging and cognitive testing were undertaken between 2010 and 2013. Generalized estimating equations were used to model associations between LVM and later imaging and cognition outcomes. The mean follow-up period was 17 years. A difference of 25 g in higher LVM was associated with marginally lower hippocampal volume (0.01%; 95% confidence interval, 0.02–0.00; P =0.001) and higher white matter grade (0.10; 95% confidence interval, 0.02–0.18; P =0.014). Functionally, participants with higher LVM tended to have slightly lower scores on the modified mini-mental state examination (0.58; 95% confidence interval, 1.08–0.08; P =0.024). The main results persisted after adjusting for blood pressure levels or vascular disease. The small overall effect sizes are partly explained by survival bias because of the high prevalence of cardiovascular disease in our population. Our findings emphasize the role of cardiovascular health in midlife as a target for the prevention of deleterious cognitive and functional outcomes in later life. Abstract : Supplemental Digital Content is available in the text.